MEMAHAMI MEKANISME CROWDFUNDING DAN MOTIVASI BERPARTISIPASI DALAM PLATFORM Kitabisa.com - March Hot Asi Sitanggang; S. Rouli Manalu (Interaksi Online, 2018)
The development of the internet is more massive with the discovery of web 2.0 facilities gave birth to a new phenomenon of crowdsourcing. Anyone can participate openly through the internet. One of the phenomenon that is the trend in the present is the crowdfunding phenomenon of raising funds openly involving the public by utilizing internet facilities. One of the most popular crowdfunding in Indonesia is crowdfunding donation based on Kitabisa.com. This research is qualitative descriptive type using two stages. The first stage is to know from the side of technology/platform by using the approach of website content analysis. The second stage is to know the motivation of donors in participating in crowdfunding using phenomenology approach. The purpose of this research is to know how crowdfunding mechanism in Indonesia in general and what factors influence people in donating. This research uses altruism theory, gotongroyong culture and social learning theory. Research subject is Kitabisa.com website and six people who have been involved in donation at Kitabisa.com at least twice the funding. The results of this study found that the development of the Internet in the era of web 2.0 brings new alternatives to the funding system. In general, crowdfunding in Indonesia using donation based. In the process of hooking the donors Kitabisa.com as platfrom adopt culture and values in Indonesian society. The individual's motivation in donating is influenced by empathy motivation, cultural motivation, and religious teachings motivation. Kitabisa.com leads the empathy of website visitors by presenting campaigns about humanity, poverty, and health as a content of comodification in Kitabisa.com. With the platform Kitabisa.com can be connected between fundraisers with donors.